Bilateral posterior lamellar corneal transplant surgery in an infant of 17 weeks old: Surgical challenges and the added value of intraoperative optical coherence tomography. Issue 4 (4th April 2022) - Muijzer, Marc B.; Kroes, Hester Y.; van Hasselt, Peter M.; Wisse, Robert P. L.
Abstract: This study aimed to describe the surgical challenges, management, and value of intraoperative optical coherence tomography in a case of a bilateral Descemet Stripping Automated Endothelial Keratoplasty corneal transplantation at 17 weeks of age for the treatment of severe posterior polymorphous corneal dystrophy resulting from a de novo mutation of the OVOL2‐gene. Abstract : We present a severe case of PPCD resulting from a rare de novo pathogenic mutation of the OVOL2 gene warranting a bilateral corneal transplantation at a young age. The direct imaging of intraoperative OCT may aid surgery in severely clouded corneas.